PERENCANAAN PRODUKSI SAOS SAMBAL UNTUK MEMINUMUMKAN TOTAL BIAYA PRODUKSI DI CV. SINAR NUGRAHA, CIREBON, JAWA BARAT - Yoga Saputra; Stefanus Soegiharto; Indri Hapsari (Perpustakaan Universitas Surabaya, 2018)
CV. Sinar Nugraha is a company engaged in manufacturing chili sauce, soy sauce, lemonade and ginger. The company is using make to stock strategies for chili sauce product which is the main product and the focus of this study. There are four brands of chili sauce manufactured by CV. Sinar Nugraha namely Sambal Panci, Sambal 2 Cabe, Sambal Harum and Sambal Wong Solo. The demand of chili sauce in CV. Sinar Nugraha are very volatile so that companies can not fulfill the demand on time and lead to lost sales at a particular time. It also appears high inventory costs due to a lack of control in determining the amount of inventory. This is occured because the company only uses estimates in production planning. The purpose of this study is to make chili sauce production planning to minimize the total cost. Aggregate production planning is a way to estimate the amount of goods that will be produced during the planning period taking into account the results of forecasting of consumer demand with production capacity of the company. Demand forecasting is done by WINQSB. Forecasting methods which was used for Sambal Panci is Winters 'Multiplicative, Sambal 2 Cabe is Multiplicative Decomposition, while Sambal Harum and Sambal Wong Solo is Winters' Additive. Results of forecasting consumer demand and the company's production capacity calculations showed that the existing production capacity is sufficient to meet consumer demand, but production planning needs to be done to minimize the total cost incurred by the company. The method used to aggregate planning is Transportation method. This method was chosen because it can provide the optimal production planning results. From the aggregate planning result, do disaggregation by linear programming methods for making production plans for each product. Having obtained the results of theproduction planning for each product, then the next step is to calculate the total cost. Calculation of the total cost derived from the sum of the production costs, inventory costs, and backorder cost. From the results of calculation using company production method acquired the total cost incurred by the company during January to September 2016 amounted to Rp 9,561,198,598.43, while the total cost derived from the calculation using proposed production method is Rp 9,264,868,346.13. So, the total cost savings gained by using proposed production methods is Rp 296,330,252.30 or 3.10%.